IFNAR2 Is Required for Anti-influenza Immunity and Alters Susceptibility to Post-influenza Bacterial Superinfections - Shepardson, Kelly M.; Larson, Kyle; Johns, Laura L.; Stanek, Kayla; Cho, Hanbyul; Wellham, Julia; Henderson, Haley; Rynda-Apple, Agnieszka (Frontiers in Immunology, 2018)
Influenza virus infections particularly when followed by bacterial superinfections (BSI) result in significant morbidities and mortalities especially during influenza pandemics. Type I interferons (IFNs) regulate both anti-influenza immunity and host susceptibility to subsequent BSIs. These type I IFNs consisting of, among others, 14 IFN-α’s and a single IFN-β, are recognized by and signal through the heterodimeric type I IFN receptor (IFNAR) comprising of IFNAR1 and IFNAR2. However, the individual receptor subunits can bind IFN-β or IFN-α’s independently of each other and induce distinct signaling. The role of type I IFN signaling in regulating host susceptibility to both viral infections and BSI has been only examined with respect to IFNAR1 deficiency. Here, we demonstrate that despite some redundancies, IFNAR1 and IFNAR2 have distinct roles in regulating both anti-influenza A virus (IAV) immunity and in shaping host susceptibility to subsequent BSI caused by S. aureus. We found IFNAR2 to be critical for anti-viral immunity. In contrast to Ifnar1-/- mice, IAV-infected Ifnar2-/- mice displayed both increased and accelerated morbidity and mortality compared to WT mice. Furthermore, unlike IFNAR1, IFNAR2 was sufficient to generate protection from lethal IAV infection when stimulated with IFN-β. With regards to BSI, unlike what we found previously in Ifnar1-/- mice, Ifnar2-/- mice were not susceptible to BSI induced on day 3 post-IAV, even though absence of IFNAR2 resulted in increased viral burden and an increased inflammatory environment. The Ifnar2-/- mice similar to what we previously found in Ifnar1-/- mice were less susceptible than WT mice to BSI induced on day 7 post-IAV, indicating that signaling through a complete receptor increases BSI susceptibility late during clinical IAV infection. Thus, our results support a role for IFNAR2 in induction of anti-IAV immune responses that are involved in altering host susceptibility to BSI and are essential for decreasing the morbidity and mortality associated with IAV infection. These results begin to elucidate some of the mechanisms involved in how the individual IFNAR subunits shape the anti-viral immune response. Moreover, our results highlight the importance of examining the contributions of entire receptors, as individual subunits can induce distinct outcomes as shown here.